Agricultural marketing and risk management strategies: an analysis of the United States livestock industry - Sancewich, Brian Robert (Kansas State University, 2014)
This dissertation examines several different issues regarding pricing and contracting decisions as well as risk management practices affecting the Unites States livestock industry. The resulting policy and market implications are applicable to industry stakeholders in the beef cattle industry. Each topic is presented in the following chapters. Chapter 1 uses time series techniques to identify movements in regional fed cattle prices under a mandatory price reporting system. Mandatory price reporting altered the structure of livestock markets by requiring supply and demand conditions to be reported twice daily thereby affecting the price discovery process. Results suggest the level of information flow and the transparency of prices increased, markets respond to new information quicker, and larger volume markets behave as a price leader to smaller markets with less volume. Chapter 2 uses closeout data to measure the variability of profits in fed cattle production. A mean-variance approach was used to model yield risk factors relevant to and known at the time cattle are placed on feed. Results indicate yield factors were influenced by several preconditioning variables such as gender, placement weight, feedlot location, placement season, and overall animal health and vitality. Estimates from the yield equations were then used to simulate the overall ex-ante distribution of expected profits for the cattle feeder and the results provide information regarding the effect of production risk and price risk on cattle feeding profits.
Keywords: Agricultural economics; Economics, Agricultural (0503)